A novel ternary metal oxide cascade Z-scheme heterojunction for efficient CO2 photoconversion without a co-catalyst. Issue 4 (August 2022) - Prajapati, Pankaj Kumar; Garg, Devesh; Malik, Anil; Kumar, Dileep; Amoli, Vipin; Jain, Suman L.
Abstract: Photocatalytic CO2 reduction to produce synthetic fuels has emerged as a promising strategy in the quest for environmentally friendly and sustainable energy sources. Herein, we report a ternary metal oxide cascade Z-Scheme consisting of Cu2 O/WO3 /CeO2 nano-heterostructures that exhibits 4-fold higher activity towards visible-light-driven photocatalytic CO2 reduction in the absence of noble metal co-catalysts compared to binary oxide components and 8-fold higher than CeO2 . The ternary Z-scheme heterojunction shows enhanced visible light absorption, effective separation of photoinduced charge carriers, and enhanced redox capacity due to the synergistic effect of two heterojunctions in Cu2 O/WO3 /CeO2 . Graphical Abstract: ga1 Highlights: A ternary nanostructured hybrid consisting of Cu2 O/WO3 /CeO2 was synthesized using a facile hydrothermal method. The ternary hybrid exhibited 4-fold higher activity for CO2 photoreduction than binary hybrid and 8-fold than CeO2 . The developed photocatalyst afforded efficient CO2 conversion without using any noble metal co-catalyst. Effective charge separation and higher absorption due to the synergistic effect of constituted heterojunctions.